Wittgenstein in the 1930s between the 'Tractatus' and the 'Investigations' - Stern, David G. (Cambridge University Press, 2018)
"The aim of this collection of fifteen previously unpublished essays is not only to provide a wide range of fresh perspectives on Wittgenstein's philosophical writing and teaching during his so-called "middle period" (roughly 1929-1936), but also to make the case for its interest and importance for our understanding of his philosophy as a whole. The exact dating of this stage of his work is itself debatable, precisely because it is understood as picking out the years after he began to rework his early philosophy, as set out in the Tractatus, and before he had arrived at the definitive formulation of his later philosophy in the Philosophical Investigations. For present purposes, we can regard it as beginning with Wittgenstein's return to Cambridge, and full-time philosophical writing, in early 1929, and ending in late 1936, when he drafted an early version of the Investigations"...
Includes bibliographical references
Keywords: Wittgenstein, Ludwig -- 1889-1951; Geschichte 1929-1936; Philosophie; Aufsatzsammlung